Vaccination, Adolescents, and the Mature Minor Standard in Ohio - Kathryn Poe (Ohio Journal of Public Health, 2025)
Controversy in recent years surrounding the vaccination of minors and the stories of adolescents like Ohioan Ethan Lindenberger, who went viral for a Reddit post in 2019 in which he asked for advice after discovering that he had never been vaccinated, have raised questions about whether allowing adolescents to vaccinate without parental consent is ac-ceptable. This article discusses the mature minor doctrine, Kantian philosophy, and principlism to argue that not only is it acceptable to do so, but there is already precedent in Ohio law, and doing so would be beneficial to public health in Ohio.
Keywords: Vaccination; Adolescents; Mature minor; Parental consent